The Salivary Estriol Level was Higher in Preterm Delivery Compared to that in Preterm Pregnancy - Purba, Erwin (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To know the difference of salivary estriol level between patients with preterm birth and preterm pregnancy of 32-36 weeks and to determine the correlation between the level of estriol in saliva and the incidence of preterm delivery. Methods: This research was a cross-sectional studies of 80 patients in Dr. Hasan Sadikin Hospital and its networks. The subjects are 40 patients in labor and 40 patients in preterm pregnancy, that met the inclusion criterias during the period September 2011 to November 2011. We took the salivary sample and examine the level of estriol. The data were analyzed by Shapiro-Wilk and Mann Whitney test. Result: The study found that the difference of salivary estriol levels in preterm labor and preterm pregnancy groups was statistically significant (p